PENGUATAN STRATEGI BRANDING UMKM PRODUKSI TELUR ASIN DI DESA SUKAMAJU KECAMATAN CIANJUR KABUPATEN CIANJUR - Dina, Dina (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2024)
Micro, Small and Medium Enterprises (MSMEs) business people often still focus on trading activities and tend to ignore the importance of branding and product legality. This phenomenon can be caused by several factors, such as lack of knowledge, selfish attitude, or closedness to new ideas and a tendency to be quickly satisfied. In the context of marketing communications, branding and product legality have a vital function as a means of instilling a positive image in the minds of consumers. Therefore, understanding the importance of branding and product legality is very necessary for business actors, because this aspect is one of the key factors so that MSME products can continue to be remembered by the public or consumers in the long term. One of the MSMEs in Sukamaju Village is